Penegakan Hukum Terhadap Penyidik Kepolisian Dalam Kasus Penangkapan Tidak Sah (Studi Kasus Pada Kepolisian Daerah Sumatera Utara) - Irka Dony Hutasoit; Taufik Siregar; Rizkan Zulyadi (Mahesa Research Center, 2022)
This study aims to examine and analyze the rule of law, law enforcement and the factors constraining the police in the case of illegal arrests at the North Sumatra Regional Police. This research is a normative juridical law research which is descriptive analytical using a statute approach. The data collection method was carried out through field research (field research), and analyzed qualitatively. The results of the study that law enforcement against investigators mentioned illegal ones based on Perkap No. 14 of 2011 concerning the Professional Code of Ethics of the Indonesian National Police, because until now there is no law that regulates sanctions for investigators who make wrong arrests. The factors faced are that there are no clear rules regarding legal sanctions for sanctions that apply to pre-trial, unclear ethical regulations against illegal sanctions, superiors who are less supportive so that they are not firm in enforcing sanctions, solidarity among members of the police to protect each other even though made a mistake in the application, the intervention of another party intentionally hinders the enforcement process of an illegal examination.